Evaluation of Pedestrian Facilities in Al-Najaf City - sadeq Hayder Ismael; Al-Jameel Hamid Athab (E3S Web of Conferences, 2023)
Less attention to pedestrian facilities significantly affects traffic flow, such as side friction and delay. It was noted that a high interaction, in Al-Najaf city, with the vehicular stream by pedestrians resulted in a reduction in the performance of this urban road network with high pedestrian interactions. Compared to vehicular movements, pedestrians continuously interact with each other and their surrounding environment, constantly changing characteristics and direction. This study aims to evaluate Al-Najaf City pedestrian facilities (Footbridges). The number and location of these bridges were investigated in 2010 and 2022 using Arc GIS10.5. Furthermore, some specific sites have been selected to indicate the intensity of interaction between the pedestrian and traffic flow. The results showed a significant lack of pedestrian footbridges in the city with high pedestrian interaction (side friction) in the selected sites.